2014
DOI: 10.3892/ijo.2014.2365
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA-203 inhibits the progression of esophageal squamous cell carcinoma with restored epithelial tissue architecture in vivo

Abstract: MicroRNA (miR)-203 has been shown to induce squamous differentiation of epidermal stem cells through the suppression of p63. The aim of this study was to assess the tumor suppressor effect of miR-203 in esophageal squamous cell carcinoma (ESCC) with focus on the regulation of the cell fate decisions and organization of tumor tissue architecture in vivo. Our investigation establishing stable clones from ESCC cell lines with induced miR-203 expression resulted in significant growth inhibition in a mouse xenograf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 34 publications
2
13
0
Order By: Relevance
“…C), finding compatible with the previous report in advanced ESCC that the expression of p75NTR is restricted in the most front layer of the infiltrative margin in diffusely proliferating ESCC lesions . Although the molecular mechanism which regulate p75NTR expression has not yet been elucidated, a recent report showed that induction of microRNA 203 into esophageal cancer cell lines resulted in restored tumor tissue polarity in vivo with expression of basement membrane proteins and localization of p75NTR expression in the basal layer, suggesting that interaction between the basal cells and basement membrane may play a role in regulation of p75NTR expression.…”
Section: Discussionsupporting
confidence: 90%
“…C), finding compatible with the previous report in advanced ESCC that the expression of p75NTR is restricted in the most front layer of the infiltrative margin in diffusely proliferating ESCC lesions . Although the molecular mechanism which regulate p75NTR expression has not yet been elucidated, a recent report showed that induction of microRNA 203 into esophageal cancer cell lines resulted in restored tumor tissue polarity in vivo with expression of basement membrane proteins and localization of p75NTR expression in the basal layer, suggesting that interaction between the basal cells and basement membrane may play a role in regulation of p75NTR expression.…”
Section: Discussionsupporting
confidence: 90%
“…The uncertainty of miR-203 function may be due to its targeted activity against numerous molecules involved in a variety of cellular functions. Some of its targets include p63, Akt2, BMI1, and LASP1 which are responsible for cellular proliferation, apoptosis, and chemoresistance (40)(41)(42)(43)(44)(45)(46). Even though our results are consistent with previously published data, we acknowledged that our study has some limitations.…”
Section: Overexpressed Mir-203 Induces Apoptosis and Decreases Cell Isupporting
confidence: 52%
“…Referring to another epithelial example, miR‐203 was shown to induce differentiation of esophageal SCC cells to restore epithelial tissue architecture and inhibit tumor growth in murine xenograft models . Another laboratory demonstrated a similar inhibitory effect of miR‐203 in vitro on esophageal cancer stem‐like cells .…”
Section: Cancer Stem Cells and Micrornasmentioning
confidence: 90%